The cross of the Son of God - Hengel, Martin; Bowden, John (London, UK SCM, 1986)
Contents includes : "The Son of God", a translation of Der Sohn Gottes. Die Entstehung der Christologies ind die judisch-hellenistische Religionsgeschichte, published 1975 by J.C.B. Mohr (Paul Steinbeck) Tubingen; "Crucifixion", a translation of "Mors turpissima crucis: Die Kreuzigung in der antiken Weltnund die "Torheit" des "Wortes vom Kreuz"," published in "Rechtfertigung. Festschrift fur Ernst Kasemann zum 70. Geburtstag", ed J. Friedrich, W. Pohlmann and P. Stuhlmacher, by J.C.B. Mohr (Paul Stenbeck), Tubingen, 1976, with substantial later additions by the author; " The atonement", originally an extended article "Der stellvertretende Suhnetod Jesu. Ein Beitrag zur Entstehung des urchristlichen Kerygmas", Internationale katholische Zeitschrift 9, 1980, 1-25, 135-147, with substantial additions by the author. Includes bibliographical references and indexes.
Compilation.
Keywords: Cross -- doctrine; Jesus Christ -- person and offices